Negotiating religious authority and identity in Digital Islam: The Ba'Alawi lineage debate in Indonesia - Amyaz Bill Aufaq (PT Perfidia Akademia, 2026)
The Ba'Alawi lineage controversy in Indonesia has generated extensive debate in digital spaces, yet previous studies have primarily focused on genealogical validity while paying limited attention to how religious authority, genealogical authenticity, digital legitimacy, and identity are negotiated online. This study examines the construction and negotiation of religious authority surrounding the Ba'Alawi lineage controversy through digital media. Employing a qualitative netnographic approach, the study analyzed 535 purposively selected YouTube comments from five videos, complemented by data from X and Google Trends. The data were analyzed using directed qualitative content analysis and thematic analysis. The findings identify four major themes: religious authority contestation, competing standards of genealogical authenticity, digital negotiation of religious legitimacy, and identity construction. The controversy has evolved from a genealogical dispute into a broader arena in which religious authority and identity are negotiated through public participation and algorithmic visibility. This study contributes to the growing scholarship on Digital Islam by demonstrating how genealogy-related controversies are transformed into negotiations of legitimacy and collective identity within digital environments. Abstrak Polemik nasab Ba'Alawi di Indonesia telah memicu perdebatan yang luas di ruang digital. Namun, sebagian besar penelitian masih berfokus pada validitas genealogi dan belum menjelaskan bagaimana otoritas keagamaan, autentisitas genealogis, legitimasi digital, dan identitas dinegosiasikan dalam diskursus daring. Penelitian ini bertujuan menganalisis konstruksi dan negosiasi otoritas keagamaan dalam polemik nasab Ba'Alawi melalui media digital. Penelitian menggunakan pendekatan kualitatif dengan metode netnografi terhadap 535 komentar YouTube yang dipilih secara purposif dari lima video, didukung oleh data dari X dan Google Trends. Data dianalisis menggunakan directed qualitative content analysis dan thematic analysis. Hasil penelitian mengidentifikasi empat tema utama, yaitu kontestasi otoritas keagamaan, persaingan standar autentisitas genealogis, negosiasi legitimasi keagamaan di ruang digital, dan konstruksi identitas. Temuan menunjukkan bahwa polemik tersebut telah berkembang dari sengketa genealogi menjadi arena negosiasi otoritas dan identitas yang dipengaruhi oleh partisipasi publik dan visibilitas digital. Penelitian ini berkontribusi pada kajian Digital Islam dengan menunjukkan bagaimana polemik genealogi bertransformasi menjadi kontestasi legitimasi dan identitas dalam ruang digital.